1979
DOI: 10.1037/h0077601
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal unit activity in the abducens nucleus during classical conditioning of the nictitating membrane response in the rabbit (Oryctolagus cuniculus).

Abstract: Neuronal unit activity was recorded from the abducens (6th nerve) nucleus, the "final common path," during classical conditioning of the nictitating membrane (NM) response in the rabbit, with the use of a tone conditioned stimulus, an air puff unconditioned stimulus (UCS), 250-msec interstimulus interval, and 60-sec intertrial interval. Animals were given 2 days of conditioning training (104 trials in eight blocks per day) and 1 day of extinction. Control animals were given comparable periods of stimulus prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 30 publications
2
30
1
Order By: Relevance
“…In mapping, we typically record multiple-unit activity, but isol~ted single-unit recording can also be done using higher impedance microelectrodes. Vnit discharges are converted to standard pulses and stored and analyzed in a computer, as described previously (Berger & Thompson, 1978;Cegavske, Patterson. & Thompson, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…In mapping, we typically record multiple-unit activity, but isol~ted single-unit recording can also be done using higher impedance microelectrodes. Vnit discharges are converted to standard pulses and stored and analyzed in a computer, as described previously (Berger & Thompson, 1978;Cegavske, Patterson. & Thompson, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…First, Lorente de No reported more than 50 years ago, in quite a different context, that cornea1 stimulation caused activation of the retractor bulbi as well as the other six extraocular muscles in rabbit. Cegavske et al (1976Cegavske et al ( , 1979 had reported that abducens multiple units were highly correlated with conditioned and unconditioned NM extension in the rabbit. Later, Harrison et al (1976) reported the same phenomenon for oculomotor nucleus multiple units.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies of motor control of the reflex and conditioned responses focused on NM extension, actually eyeball retraction, controlled mostly (but not entirely) by the retractor bulbus muscle, innervated largely by axons of the sixth nerve originating in the accessory abducens (and to a much lesser extent, abducens) nuclei. However, the other extraocular muscles also contract synergistically with the retractor bulbus or relax in an antagonistic manner in the case of the levator palpebrae motor neurons (Cegavske et al 1976(Cegavske et al , 1979(Cegavske et al , 1987Berthier et al 1987;Disterhoft et al 1987). At the time there was much debate about the details of innervation of the retractor bulbus muscle, which in retrospect was somewhat irrelevant because the most prominent and sensitive component of the response is EMG activity in the orbicularis oculi muscle controlling external eyelid closure ), innervated by the seventh nerve from the facial nucleus.…”
Section: The Ur Pathwaysmentioning
confidence: 99%